Mosquito transmission, growth phenotypes and the virulence of malaria parasites. - Pollitt, L; Mackinnon, M; Mideo, N; Read, A (2013)
BACKGROUND: A series of elegant experiments was recently published which demonstrated that transmission of malaria parasites through mosquitoes elicited an attenuated growth phenotype, whereby infections grew more slowly and reached peak parasitaemia at least five-fold lower than parasites which had not been mosquito transmitted. To assess the implications of these results it is essential to understand whether the attenuated infection phenotype is a general phenomenon across parasites genotypes and conditions. METHODS: Using previously published data, the impact of mosquito transmission on parasite growth rates and virulence of six Plasmodium chabaudi lines was analysed. RESULTS: The effect of mosquito transmission varied among strains, but did not lead to pronounced or consistent reductions in parasite growth rate. CONCLUSIONS: Mosquito-induced attenuated growth phenotype is sensitive to experimental conditions.